Motor unit firing frequency of lower limb muscles during an incremental slide board skating test - Piucco, T.; Bini, R.; Sakaguchi, M.; Diefenthaeler, F.; Stefanyshyn, D. (Sports Biomechanics, 2017)
This study investigated how the combination of workload and fatigue affected the frequency components of muscle activation and possible recruitment priority of motor units during skating to exhaustion. Ten male competitive speed skaters performed an incremental maximal test on a slide board. Activation of six muscles from the right leg was recorded throughout the test. A time-frequency analysis was performed to compute overall, high, and low frequency bands from the whole signal at 10, 40, 70, and 90% of total test time. Overall activation increased for all muscles throughout the test (p<0.05 and ES>0.80). There was an increase in low frequency (90 vs. 10%, p=0.035, ES=1.06) and a decrease in high frequency (90 vs. 10%, p=0.009, ES=1.38, and 90 vs. 40%, p=0.025, ES=1.12) components of gluteus maximus. Strong correlations were found between the maximal cadence and vastus lateralis, gluteus maximus and gluteus medius activation at the end of the test. In conclusion, the incremental skating test lead to an increase in activation of lower limb muscles, but only gluteus maximus was sensitive to changes in frequency components, probably caused by a pronounced fatigue. ABSTRACT FROM AUTHOR